2021
DOI: 10.1016/j.ekir.2021.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Frailty: Challenges in Mainstream Nephrology Practice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 101 publications
0
28
0
5
Order By: Relevance
“…However, protein restriction may inhibit hepatic albumin synthesis [ 138 ], which might be further suppressed by inflammatory signals [ 139 ], characterizing DN [ 140 ]. Furthermore, diabetes [ 141 ] as well as CKD [ 142 ] are associated with sarcopenia, and the likelihood of sarcopenia among diabetics increases 2.54-fold in the presence of DN [ 141 ]. Renal protein wasting, discussed above, possibly contributes to sarcopenia, and intuitively one would favor enriched protein intake rather than a low-protein diet specifically in this population.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…However, protein restriction may inhibit hepatic albumin synthesis [ 138 ], which might be further suppressed by inflammatory signals [ 139 ], characterizing DN [ 140 ]. Furthermore, diabetes [ 141 ] as well as CKD [ 142 ] are associated with sarcopenia, and the likelihood of sarcopenia among diabetics increases 2.54-fold in the presence of DN [ 141 ]. Renal protein wasting, discussed above, possibly contributes to sarcopenia, and intuitively one would favor enriched protein intake rather than a low-protein diet specifically in this population.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Biologisch alte Dialysepatienten haben geringe physiologische Reserven und damit ein erhöhtes Risiko für Krankheit und Tod. Diese Besonderheiten alter Dialysepatienten beschreibt am besten das Frailty-Konzept: Der angelsächsische Begriff beschreibt eine erhöhte Vulnerabilität infolge zunehmender Anhäufung körperlicher und psychosozialer Defizite infolge eines altersbedingten Abbaus verschiedener Organsysteme 6 , 7 . Frailty ist damit nicht identisch mit Multimorbidität und Gebrechlichkeit, aber ein Konzept für das erhöhte gesundheitliche Risiko während des Alterns.…”
Section: Der Alte Dialysepatientunclassified
“…bioelektische Impedanzanalyse (BIA): misst den Ernährungszustand und die Muskelmasse 6 , 20 , 29 , 30…”
Section: Physical Performance: Testen Messen Verfolgenunclassified
See 1 more Smart Citation
“… 9 Based on data from 41 randomised controlled trials (RCT), Heiwe et al reported practical improvements in aerobic capacity, muscular function and walking capacity in patients with CKD after exercise, 10 indicators that are the core of frailty. 11 In other words, exercise is an essential non-pharmacological strategy to improve frailty symptoms in patients with CKD, the latter being a significant cause of sedentary behaviour in such population. 12 Because of this, some researchers and guidelines recommend that healthcare providers prescribe exercise for patients with CKD.…”
Section: Introductionmentioning
confidence: 99%